PENERAPAN HUKUM TERHADAP PERLINDUNGAN PEKERJA KONTRAK DI INDOMARET (STUDI DI KECAMATAN SINTANG KABUPATEN SINTANG - Rini Safarianingsih (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2020)
The protection of labour in Indonesia must be carried out by each entrepreneur or company that hire employee to work for the company for the purpose to have a responsibility toward the maintenance and the improvement of welfare, it is carried out as labour social security form which plays such commonly implemented or as a primary, provides a decent wage, an appropriate working hours based on the applicable regulations and the workers’ rights. The method used by the researcher is a sociological juridical approach with an descriptive research analysis. In data collecting, this reasearch used a field studies and literature. Moreover, the reasearcher used qualitative-descriptive for technique data analysing; the author does not use lists of tables, numbers and statistical formulas in thesis writing. The result of this research are; there is an employees of Indomaret occupied call as contract worker for 2 years and it is extended for 2 years continuously. In during that process the workers’ rights have not been fulfilled and the worker efforts their rights through deliberation but it does not got results. In conclusion, there is no protection regarding with the employment agreement in the specific time as stated in article 59 paragraph (2) and paragraph (4) which states that PKWT cannot be implemented for a permanent employee and in a period of more than 3 (three) years with a contract extension every once a year. Moreover, it can be interpreted in paragraph (7) which stated that the violations of Article 59 paragraph (2) and paragraph (4) this will result in the PKWT being legally changed to PKWTT. This research suggests several point of view, namely: to apply a legal protection to contract workers in accordance with the labour law, every workers has the rights that must be given, especially in the fields of wages, occupational safety and health. Likewise, for a contract workers who have not receive their rights as workers are required to seek settlement through an industrial relations quarrels.